Dreams come true: youth entrepreneurs in eSikhawini township, Richards Bay - Manqoyi, Ayanda (Department of Chemical Engineering, 2016)
This research project examines the emergence of youth entrepreneurs in the moments just before mining and industrial activities develop within a community. It focuses on how young people engage with the hopes and promise of opportunities engendered by the expansion of mines and industry within a particular place. Using ethnography as methodology, it looks at how young people's dreams and desires in eSikhawini, a township in the Richards Bay area within the uMhlathuze Municipality, are activated by the coming of mining activities and how they use these to create entrepreneurs. In the context of mining and industrial expansion, young people use the promise of opportunity and the pursuit of dreams and desires to create particular kinds of entrepreneurs who attempt to stabilize their lives and that of their community in the face of precarity. It argues that the interrelations emergent in the daily enterprise of creating a stable future are key resources and insurance against uncertainty that sustain "community" in the context of eSikhawini. Overall, the thesis attempts to demonstrate that by recognising and strengthening youth entrepreneurs' capacity to aspire and realise their dreams can entrepreneurship interventions and programmes foster and sustain empowering relationships amongst marginalized people living in areas affected by mining and mineral beneficiation.